RELATIONSHIP ANALYSIS ICARE-ORIENTED STUDENTS WORKSHEET DEVELOPMENT WITH LEARNING STYLES TO IMPROVE LEARNING OUTCOMES - Sinuraya, Jurubahasa; Panggabean, Deo Demonta; Wahyuni, Ida (Advances in Social Sciences Research Journal, 2018)
This study is the first year of three years. This study aims to describe the relationship of the development of teaching materials to learning styles in improving learning outcomes. The type of research used in the entire study is Research and Development (R & D). Research subjects are lecturers and Students in Basic of Mathematics and Sciences Group. The first year’s study contains the need assessment, and the drafting of the initial draft of textbooks for high school physics courses with ICARE-oriented Students Worksheet. Data collection techniques used were questionnaire, observation, interview, and documentation study, and supported by logbooks and focus group discussion (FGD). The results shown in the development of the device indicate that the development of ICARE-based teaching materials is not influenced and does not have a significant relationship in one of the learning styles.